Current Ophthalmology Reports - Perez, Victor; SpringerLink (Online service) (New York : Springer US : Imprint: Springer.)
This journal aims to offer expert review articles on the most significant recent developments in the field of ophthalmology. By providing clear, insightful, balanced contributions, the journal intends to serve those who diagnose, treat, manage, and prevent ocular conditions and diseases. We accomplish this aim by appointing international authorities to serve as Section Editors in key subject areas across the field. Section Editors select topics for which leading experts contribute comprehensive review articles that emphasize new developments and recently published papers of major importance, highlighted by annotated reference lists. An Editorial Board of more than 20 internationally diverse members reviews the annual table of contents, ensures that topics include emerging research, and suggests topics of special importance to their country/region. Topics covered may include age-related macular degeneration; diabetic retinopathy; dry eye syndrome; glaucoma; pediatric ophthalmology; ocular infections; refractive surgery; and stem cell therapy.
Keywords: Ophthalmology; Ophthalmology